Late-term topical tacrolimus for subepithelial infiltrates resistant to topical steroids and ciclosporin secondary to adenoviral keratoconjunctivitis. Issue 5 (20th June 2020) - Arici, Ceyhun; Mergen, Burak
Abstract : Purpose: Investigation of the efficacy and safety of 12 months of topical tacrolimus 0.03% ointment treatment against the subepithelial infiltrates (SEIs) due to adenoviral keratoconjunctivitis (AKC) resisting at least 2 years was aimed. Methods: This case series included consecutive patients with SEIs secondary to AKC who were resistant to topical steroid and ciclosporin-A (CSA) treatment and treated with topical 0.03% tacrolimus (Protopic; Fujisawa Healthcare, Teva, Deerfield, Illinois, USA) for 12 months, at least 2 years after AKC. For the evaluation of treatment efficacy, best-corrected visual acuity (BCVA), Fantes score, corneal subepithelial infiltrate score (CSIS), Oxford score, Schirmer and tear breakup time results were evaluated. Intraocular pressure and complaints of the patients were followed for evaluating the safety profile of the treatment. The patients were followed after the baseline visit at the 1st, 3rd, 6th and 12th month. Results: 15 eyes of 11 patients with SEIs and 16 eyes of 16 healthy controls were included in this study. 1 patient (9.1%) could not tolerate the treatment. Significant improvements in BCVA, CSIS, Fantes score and Schirmer results were observed in the study group starting from the 3rd-month visit, and the improvements persisted until the end of 12 months of treatment. Conclusion: Topical 0.03% tacrolimus might show efficacy against the SEIs persisting at least 2 years despite corticosteroid and/or CSA treatment without any prominent side effect. While at least a period of 3 months was necessary for a significant improvement in the BCVA, SEIs and Schirmer results, a period of 6 months was necessary for a decrease in Oxford score.